2009
DOI: 10.1371/journal.pone.0005570
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Caspase Activity Regulates Skeletal Muscle Regeneration and Function in Response to Vasopressin and Tumor Necrosis Factor

Abstract: Muscle homeostasis involves de novo myogenesis, as observed in conditions of acute or chronic muscle damage. Tumor Necrosis Factor (TNF) triggers skeletal muscle wasting in several pathological conditions and inhibits muscle regeneration. We show that intramuscular treatment with the myogenic factor Arg8-vasopressin (AVP) enhanced skeletal muscle regeneration and rescued the inhibitory effects of TNF on muscle regeneration. The functional analysis of regenerating muscle performance following TNF or AVP treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…during physical exercise (40), and AVP injection improves in vivo muscle regeneration (41). Based on these observations, AVP is likely to play a physiological role in skeletal muscle development and homeostasis.…”
Section: Discussionmentioning
confidence: 97%
“…during physical exercise (40), and AVP injection improves in vivo muscle regeneration (41). Based on these observations, AVP is likely to play a physiological role in skeletal muscle development and homeostasis.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it would not be surprising if the deficits in muscle fiber regeneration and recovery seen in Hsp70 −/− mice in this study are also related to impairments in protein quality control due to the absence of intracellular Hsp70. It is well documented that upregulation of intracellular Hsp70 in skeletal muscle protects against muscle damage, enhances regenerating fiber size, promotes functional sparing and preserves myofiber size during atrophy conditions [8], [16], [17], [18], [59]. Perhaps the most striking finding related to Hsp70 overexpression was the recent study published by Gehrig et al, who demonstrated that Hsp70 transgenic overexpression in skeletal muscle and/or pharmacological induction of Hsp70 could improve muscle quality and function in a mouse model of muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle wasting contributes substantially to morbidity in septic shock and is contributed to by inhibition of muscle regeneration by TNF. Vasopressin counteracted the effects of TNF in myocyte cell cultures [62] .…”
Section: The Effects Of Vasopressin On Other Organ Dysfunctionmentioning
confidence: 95%